Obdavčitev knjižničnih publikacij - Razboršek, Robert (Knjižnica, 2005)
The aim of this article is to stimulate the unified practice of the settlement of value added tax. This article draws from international and domestic law sources, which are fundamental for the taxation in Slovenia. As a rule, library publications are taxed with a 20% rate of value added tax, for imports into the European Union as well as within the European Union. The exception are printed publications which are, in the European Union, taxed with the lower, 8,5% rate and are tax exempt for imports from non-member countries of the European Union. The interlibrary loan is still entirely tax exempt, regulated as in the rest of Europe and abroad. If the purchases are made from other European Union countries or from countries outside the EU, from the perspective of the nacional economy, the so called self-taxation in the country receiving library publications is strongly supported.
Keywords: bibliotekarstvo; library science; knjižnice; knjižnično gradivo; davek na dodano vrednost; Slovenia; Slovenija